2017
DOI: 10.1148/radiol.2017161607
|View full text |Cite
|
Sign up to set email alerts
|

Fructose-1,6-Bisphosphatase 1 Reduces18F FDG Uptake in Hepatocellular Carcinoma

Abstract: To determine whether fructose 1,6-bisphosphatase 1 (FBP1) expression is associated with fluorine 18 (18 F) fluorodeoxyglucose (FDG) accumulation in patients with hepatocellular carcinoma (HCC) and to investigate how FBP1 expression and 18 F FDG uptake are related to tumor differentiation grade and metabolism and whether the molecular mechanism involves hypoxia-inducible factor 1-a (HIF1A) transcriptional activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 34 publications
2
18
1
Order By: Relevance
“…A major concern is our patient's prognosis, given that her HCC was poorly differentiated. Chen et al showed that the SUVmax is higher in patients with poorly differentiated HCC than in those with well-or moderately differentiated counterparts; the median SUVmax of poorly differentiated HCCs in their study was 6.7 (17), while that of our patient was much higher at 12.82. Indeed, the area in the liver tumor showing an abnormal fluorodeoxyglucose uptake corresponded with the hypovascular area detected on dynamic CT, which suggested that this area could have high malignancy.…”
Section: Figure 2 On Ethoxybenzyl-magnetic Resonance Imaging Performcontrasting
confidence: 56%
“…A major concern is our patient's prognosis, given that her HCC was poorly differentiated. Chen et al showed that the SUVmax is higher in patients with poorly differentiated HCC than in those with well-or moderately differentiated counterparts; the median SUVmax of poorly differentiated HCCs in their study was 6.7 (17), while that of our patient was much higher at 12.82. Indeed, the area in the liver tumor showing an abnormal fluorodeoxyglucose uptake corresponded with the hypovascular area detected on dynamic CT, which suggested that this area could have high malignancy.…”
Section: Figure 2 On Ethoxybenzyl-magnetic Resonance Imaging Performcontrasting
confidence: 56%
“…There is some evidence that the expression of these two molecules correlates with patient response [8], such that determining their expression levels prior to initiation of checkpoint therapy may help stratify patients and select the proper treatment. These authors have conducted similar 18 F-FDG correlation studies in other types of cancer previously [9][10][11], and have shown relationships between FDG uptake and FBP1 expression in hepatocellular carcinoma, HER2 expression in gastric cancer, and LDHA levels in lung adenocarcinoma. Likewise, PD-L1 expression has been found by other groups to be correlated with FDG uptake in lung cancer [12,13].…”
mentioning
confidence: 86%
“…FBP1 is a gluconeogenic enzyme that is upregulated in response to fructose exposure [33]. Clinical research has shown that low FBP1 expression is associated with poorer survival and more aggressive HCC growth [119][120][121][122][123][124]. Low FBP1 expression enhances glycolysis in HCC [122,124], while increasing FBP1 reduced GLUT1 expression, glucose uptake, lactate production, and cell growth [120,121,123].…”
Section: Genetic Changes Associated With Hcc May Reduce Fructose Metamentioning
confidence: 99%